2021
DOI: 10.1002/essoar.10505548.1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Moments View of Climatology and Variability of the Asian Summer Monsoon Anticyclone

Abstract: A comprehensive investigation of the climatology of and interannual variability and trends in the Asian summer monsoon anticyclone (ASMA) is presented, based on a novel area and moments analysis. Moments include centroid location, aspect ratio, angle, and ''excess kurtosis'' (measuring how far the shape is from elliptical) for an equivalent ellipse with the same area as the ASMA. Key results are robust among the three modern reanalyses studied. The climatological ASMA is nearly elliptical, with its major axis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 42 publications
3
7
0
Order By: Relevance
“…Our study also shows that quadrupling of the normalCnormalO2 in coupled models leads to an equatorward shift of the ASM anticyclone, which is in agreement with a recent study by Manney et al. (2021), showing a strong positive correlation in the location between the anticyclone and subtropical westerly jet. Yet, the cause and effect remains unclear and is a subject of future investigations.…”
Section: Response Of 100 Hpa Global Circulation To Quadrupled Co2supporting
confidence: 93%
See 1 more Smart Citation
“…Our study also shows that quadrupling of the normalCnormalO2 in coupled models leads to an equatorward shift of the ASM anticyclone, which is in agreement with a recent study by Manney et al. (2021), showing a strong positive correlation in the location between the anticyclone and subtropical westerly jet. Yet, the cause and effect remains unclear and is a subject of future investigations.…”
Section: Response Of 100 Hpa Global Circulation To Quadrupled Co2supporting
confidence: 93%
“…The strengthening and equatorward expansion of the zonal‐mean subtropical upper tropospheric westerly jet is a very robust result in models and is closely connected to the enhanced warming in tropical upper troposphere (Li et al., 2009, 2010; McLandress & Shepherd, 2009; Menzel et al., 2019). Previous studies of the upper tropospheric jets showed a close connection between variability of the subtropical westerly jet and the upper level anticyclones (Manney & Hegglin, 2018; Manney et al., 2014, 2021; Schiemann et al., 2009). Our study also shows that quadrupling of the normalCnormalO2 in coupled models leads to an equatorward shift of the ASM anticyclone, which is in agreement with a recent study by Manney et al.…”
Section: Response Of 100 Hpa Global Circulation To Quadrupled Co2mentioning
confidence: 81%
“…The 2017 Asian monsoon season was not marked by an anomalous dynamical behaviour (Manney et al, 2021); however, the campaign occurred during a break-to-active transition. The strongest convective activity took place in late July and early August above the southern slopes of the Himalayas and the Tibetan Plateau, as can be inferred from the low outgoing longwave radiation (OLR) displayed as dashed contours in Fig.…”
Section: Satellite Perspectivementioning
confidence: 95%
“…The details of the bimodal distribution are sensitive to the use of different reanalysis data sets (Nützel et al., 2016), and bimodality is potentially driven by variations in convection (e.g., Garny & Randel, 2013), monsoonal heating (e.g., P. Zhang et al., 2016), orographic effects (Q. Zhang et al., 2002; Liu et al., 2007), and large‐scale dynamical variability (Amemiya & Sato, 2020). More recent analyses have highlighted that the AMA is subject to large dynamical variability on synoptic scales, constantly splitting, merging, and shedding anticyclonic eddies westward and eastward (Garny & Randel, 2013, 2016; Manney et al., 2021; Pan et al., 2016; P. M. Rupp & Haynes, 2020). C. J. Hsu and Plumb (2000) showed that an idealized monsoon anticyclone circulation periodically sheds secondary anticyclones due to dynamical instabilities, and observational confirmation of eddy shedding was first shown in Popovic and Plumb (2001).…”
Section: Introductionmentioning
confidence: 99%